An extension of Biot's theory with molecular influence based on mixture coupling theory: Mathematical model. (15th May 2020) - Ma, Yue; Chen, Xiao-Hui; Yu, Hai-Sui
Abstract: Biot's hydro-mechanical coupled consolidation theory has been widely used in Geotechnical Engineering for nearly 100 years. However, the Chemically Disturbed Zone (CDZ) generated in many geotechnical engineering applications (e.g. nuclear waste disposal, carbon capture and storage etc.) are not considered by Biot's theory, especially where there are highly swelling rocks (e.g. shale) and dissolving minerals. This paper presents a rigorous fundamental extension of Biots consolidation theory, with comprehensively considering the influence of molecular processes of coupled swelling and mineral dissolution, based on the newly developed Mixture Coupling Theory. A simple numerical example has been used for the demonstration purpose of the new constitutive equations, and the result shows that molecular influence can have a significant impact on the mechanical performance of the rocks.